2008
DOI: 10.1016/j.febslet.2008.01.026
|View full text |Cite
|
Sign up to set email alerts
|

In vitro regulation of CaCO3 crystal polymorphism by the highly acidic molluscan shell protein Aspein

Abstract: Biominerals, especially molluscan shells, generally contain unusually acidic proteins. These proteins are believed to function in crystal nucleation and inhibition. We previously identified an unusually acidic protein Aspein from the pearl oyster Pinctada fucata. Here we show that Aspein can control the CaCO 3 polymorph (calcite/aragonite) in vitro. While aragonite is preferentially formed in Mg 2+ -rich solutions imitating the extrapallial fluids of marine molluscs, Aspein exclusively induced calcite precipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
81
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 28 publications
4
81
0
Order By: Relevance
“…To investigate the crystal precipitation process, the ionic composition of the extrapallial fluid of marine molluscs, with a high Mg 2ϩ content (50 mM) relative to Ca 2ϩ (10 mM) (62), must be taken into consideration. In solution, Mg 2ϩ is harmful to calcite precipitation; this is why aragonite crystals become dominant in Mg 2ϩ -rich solutions (23). Consequently, for an efficient process of calcitic prismatic layer calcification, some regulatory factors are required to override this spontaneous condition to form calcite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the crystal precipitation process, the ionic composition of the extrapallial fluid of marine molluscs, with a high Mg 2ϩ content (50 mM) relative to Ca 2ϩ (10 mM) (62), must be taken into consideration. In solution, Mg 2ϩ is harmful to calcite precipitation; this is why aragonite crystals become dominant in Mg 2ϩ -rich solutions (23). Consequently, for an efficient process of calcitic prismatic layer calcification, some regulatory factors are required to override this spontaneous condition to form calcite.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have revealed that these highly acidic proteins can decide the calcium carbonate polymorphism in vitro (2,12,21,22). One striking example is Aspein (12,23), which acts as a crystal nucleator to induce calcite precipitation using the mechanism of ionotropy, and it is therefore crucial for the formation of the prismatic layer. In contrast, basic matrix proteins exclusively associated with the prismatic layer have been far less studied.…”
mentioning
confidence: 99%
“…Characteristic Raman bands for calcite and aragonite were assigned as described elsewhere. [6][7][8][9] Calcite and aragonite are two common polymorphs of CaCO3 observed as biominerals.…”
mentioning
confidence: 99%
“…Characteristic Raman bands for calcite and aragonite were assigned as described elsewhere. [6][7][8][9] Calcite and aragonite are two common polymorphs of CaCO3 observed as biominerals.Stony coral forms needle-like aragonite crystals, but soft coral forms only calcite crystals. The protein-induced chemical structure in calcified organisms is an important factor contributing to their growth, but until now no direct evidence has been reported.…”
mentioning
confidence: 99%
“…in regulating and controlling CaCO 3 crystals growth and orientation, determining the shape, size and polymorph [24][25][26][27][28][29], maintaining the mechanical performances [18], even displaying enzymatic functions [30] and involving in cell signalling [31]. Currently, there is a great deal of work relating with the purification and characterization of proteins from mollusk shell [32][33][34][35][36][37][38].…”
Section: Yang Et Almentioning
confidence: 99%